Mental training program in racket sports: A systematic review - Valérian Cece; Emma Guillet-Descas; Guillaume Martinent (International Journal of Racket Sports Science, 2020)
The mental aspect is largely acknowledged by athletes and coaches as a salient factor explaining performance variability. The mental component of performance holds a special place in racket sports considering the inherent demands in such intense and emotional activities. The importance of mental skills in racket sports has been examined within the literature through a bulk of studies highlighting associations between mental skills and a wide range of positive outcomes. Access to the programs which aim to improve the mental skills of the athletes represents a major issue for researchers and the different stakeholders (coaches, athletes, parents). The main objectives of this study were to (a) Collect the studies that incorporate mental training programs used in racket sports, (b) Organize the current knowledge on mental training programs and provide a synthesis of the characteristics of these studies, and (c) Identify the gaps in the literature on this topic and propose potential further investigations and practical implications. The present systematic review included 27 studies which involved 715 participants. Most of the studies used a quantitative approach and were conducted on tennis. The mental skills developed varied across the studies with domination of imagery and relaxation techniques. Overall, the programs led to positive outcomes on performance indicators (e.g. improvement of service efficacy and stroke quality) and permitted the development of the targeted mental skills (e.g. concentration, motivation). This review highlighted the weak representation of females and novice players within the studies’ participants. Moreover, the unequal representation of the techniques and outcomes in the examined studies encourages the development of further mental programs specifically applied to the demands of racket sports and a focus on different mental skills (e.g. emotional intelligence, coach education).